Detection of the ETV6-NTRK3 translocation in cutaneous mammary-analogue secretory carcinoma. Issue 12 (December 2015) - Hyrcza, Martin D.; Ng, Tony; Crawford, Richard I.
Abstract: Mammary-analogue secretory carcinoma (MASC) is a recently described salivary gland tumour with a characteristic ETV6-NTRK3 translocation found in majority of the cases. MASC has also been reported three times as primary skin tumour; however, none of these cases showed the translocation. We recently encountered a case of an asymptomatic cutaneous nodule in the axilla of a 40-year old woman which presented clinically and radiologically as an epidermoid ("sebaceous") cyst. As the tumour showed histologic and immunohistochemical findings indistinguishable from MASC of the salivary gland, we tested it for the presence of the ETV6-NTRK translocation by fluorescence in-situ hybridization using a break-apart ETV6 probe, and by real-time reverse-transcriptase PCR with primers to exon 5 of ETV6 and exon 15 of NTRK3 . The presence of the translocation was shown by both methods. Since the lesion presented clinically and radiographically as benign epidermoid cyst it is possible that other cutaneous MASC cases were previously seen but went unrecognized and misdiagnosed as other low grade cutaneous neoplasms.